2019
DOI: 10.1186/s40529-019-0263-0
|View full text |Cite
|
Sign up to set email alerts
|

Comparative transcriptome analysis reveals the genetic basis underlying the biosynthesis of polysaccharides in Hericium erinaceus

Abstract: Background Hericium erinaceus , also known as lion’s mane mushroom, is a widely distributed edible and medicinal fungus in Asian countries. H. erinaceus harbors diverse bioactive metabolites with anticancer, immunomodulating, anti-inflammatory, antimicrobial, antihypertensive, antidiabetic and neuroprotective properties. Although the chemical synthesis processes of these bioactive metabolites are known, the biosynthetic processes remain unknown. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
21
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(21 citation statements)
references
References 43 publications
0
21
0
Order By: Relevance
“…However, polysaccharides are one of the main components, which plays a variety of biological functions (Wang and Meng, 2015;Zhang et al, 2019b). Research has revealed that BSP not only facilitates coagulation by inducing the expression of vascular endothelial growth factor (VEGF), but also prevent gastric ulcers by forming a protective film that coats the stomach wall, and is a common immune modulator.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, polysaccharides are one of the main components, which plays a variety of biological functions (Wang and Meng, 2015;Zhang et al, 2019b). Research has revealed that BSP not only facilitates coagulation by inducing the expression of vascular endothelial growth factor (VEGF), but also prevent gastric ulcers by forming a protective film that coats the stomach wall, and is a common immune modulator.…”
Section: Introductionmentioning
confidence: 99%
“…With the development and implementation of advanced DNA sequencing technologies, the biological metabolisms of active components may be discerned in medicinal plants (Fu et al, 2019;Liang et al, 2019;Niazian, 2019). There are few studies on the biosynthesis of polysaccharides (this research has focused primarily on fungal species) due to their unique structures and large molecular weights (Ribeiro et al, 2012;Zhang et al, 2019b). The biosynthesis pathways of Ganoderma lucidum polysaccharides provide a preliminary study of the various synthesis pathways of medicinal plants (Gao et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…Among them, GDP-Man and UDP-Glc are mainly derived from fructose-6-phosphate and glucose-6-phosphate, while other NDP-sugars are mainly converted from UDP-Glc under the actions of isomerase, dehydrogenase, and decarboxylase (Yin et al, 2011). Glucose-6-phosphate has two important metabolic branches, a fructose-6-P branch and a glucose-1-P branch; therefore, enzymes that catalyze these two branch reactions are most important in the biosynthesis of polysaccharides (Zhang et al, 2019). According to the results of the present study, the gene expression of these enzymes showed different changing trends.…”
Section: Biosynthesis Pathway Of Polysaccharidesmentioning
confidence: 99%
“…For instance, Tan et al confirmed that a total of 48 differential expressed genes were related to polysaccharide synthesis and carbohydrate metabolism in G. lucidum by high-throughput RNAsequencing (RNA-seq) [15]. Simultaneously, many genes of H. erinaceus involved in polysaccharide biosynthesis were identified using RNA-seq, and these transcripts encoded the key-enzymes related to polysaccharide biosynthesis, including PGM, UGP, and PGI [16]. However, few studies have reported the critical regulatory genes or key enzymes in the biosynthesis pathway of H. erinaceus polysaccharide.…”
Section: Introductionmentioning
confidence: 99%